Mixtures of organic amendments and biochar promote beneficial soil microbiota and affect Fusarium oxysporum f. sp. lactucae, Rhizoctonia solani and Sclerotinia minor disease suppression. (5th December 2021) - Bonanomi, Giuliano; Zotti, Maurizio; Idbella, Mohamed; Cesarano, Gaspare; Al‐Rowaily, Saud L.; Abd‐ElGawad, Ahmed M.
Abstract: The use of soil fumigants and fungicides to control soilborne pathogens is reduced due to awareness of their negative drawbacks. Long‐term application of such agrochemicals negatively affects soil microbiota and reduces natural soil suppressiveness. We investigated long‐term impacts of biochar and not‐pyrogenic organic amendment (OAs: manure, alfalfa straw and glucose), on disease suppression compared with conventional management in three pathosystems: Fusarium oxysporum f. sp. lactucae (FOL)–lettuce, Rhizoctonia solani –tomato and Sclerotinia sclerotiorum –lettuce, by conditioning soil for 2 years. Soil analyses included pH, electrical conductivity, organic carbon, total nitrogen, C:N ratio, N‐NO3 −, N‐NH4 +, cation exchange capacity, available phosphorus, Ca 2+, Mg 2+, K +, Na +, fluorescein diacetate (FDA), and total and active limestone. Soil microbiota was characterized by combining BIOLOG EcoPlates with next‐generation sequencing of 16S and 18S rRNA genes. Soil amended with OAs generally suppressed disease by S . sclerotiorum and FOL compared to fumigants and synthetic fertilizers. However, the incidence of R . solani infection was lower in soil treated with synthetic fertilizers than soil amended with OAs. EC, pH, C:N, N‐NO3 −, N‐NH4 +, FDA and BIOLOG were significantly correlated with disease, depending on pathosystem. Bacterial richness and diversity, presence of some genera like Acidobacteria, Chloracidobacteria, Solibacteres, Anaerolineae, Nitrospira and Deltaproteobacteria were negatively related to disease incidence of FOL and S . sclerotiorum, whereas damping‐off caused by R . solani was negatively affected by the presence of Flavobacterium and Chitinofagha . Therefore, we concluded that long‐term application of OAs can effectively improve soil suppressiveness and reduce disease incidence against root pathogens, although the effects vary considerably depending upon pathosystem. Abstract : Soil long‐term application with organic amendments and biochar combination can efficiently improve soil suppressiveness and reduce disease incidence against root pathogens, depending upon the pathosystem.